THE CONCRETE BEAMS WORK WITH EXTERNAL SHEET REINFORCEMENT - Halahuria, Ye. Yu. (Science and Transport Progress, 2007)
The author presents the results of testing four series of concrete beams. The experiential trials were performed in order to study the joint work of concrete core and steel plate, united by the anchors and different types of glue.